Age- and sex-specific reference intervals across life span for insulin-like growth factor binding protein 3 (IGFBP-3) and the IGF-I to IGFBP-3 ratio measured by new automated chemiluminescence assays - Friedrich, Nele; Wolthers, Ole D; Arafat, Ayman M; Emeny, Rebecca T; Spranger, Joachim; Roswall, Josefine; Kratzsch, Jürgen; Grabe, Hans J; Hübener, Christoph; Pfeiffer, Andreas F H; Döring, Angela; Bielohuby, Maximilian; et al. (The journal of clinical endocrinology and metabolism, 2014)
Measurement of IGF-binding protein-3 (IGFBP-3) can aid the diagnosis of GH-related diseases. Furthermore, epidemiological studies suggest that IGFBP-3 and the molar IGF-I to IGFBP-3 ratio are associated with clinical end points like cancer or cardiovascular disease. However, their clinical use is limited by the lack of validated reference intervals. The objective of the study was the establishment of age- and sex-specific reference intervals for IGFBP-3 and the molar IGF-I to IGFBP-3 ratio by newly developed automated immunoassays. This was a multicenter study with samples from 11 cohorts from the United States, Canada, and Europe. A total of 14 970 healthy subjects covering all ages from birth to senescence participated in the study. Concentrations of IGFBP-3 and the IGF-I to IGFBP-3 ratio as determined by the IDS iSYS IGF-I and IGFBP-3 assays were measured. Both the concentration of IGFBP-3 and the IGF-I to IGFBP-3 ratio are mainly determined by age. IGFBP-3 concentrations increase until the age of 22 years, with a plateau being visible between 15 and 25 years. Determined by the high peripubertal peak in IGF-I, the peak in the IGF-I to IGFBP-3 ratio occurs already around the age of 15 years, with a slightly earlier and higher peak in females. Beyond the age of 60 years, IGFBP-3 concentrations remain higher in females, whereas IGF-I as well as the IGF-I to IGFBP-3 ratio remains significantly higher in males. We present an extensive set of assay-specific age- and sex-adjusted normative data for concentrations of IGFBP-3 and the molar IGF-I to IGFBP-3 ratio and demonstrate distinct sex specific differences across the life span.